The teaching of coastal folk dance in the training students (RIAF. International Journal of Physical Activity, 2023)
Recovering the Ecuadorian Cultural identity continues to be a topic of great interest; In the case of the students of the Faculty of Physical Education, Sports and Recreation, the foregoing acquires great value, precisely because of the contribution that coastal folkloric dance offers in the folklore class, which facilitates the integral development of young people. The main objective of the study focuses on the innovation of pedagogical strategies oriented to practice during the folklore class, also generating spaces in the various areas of study and thus creating people aware of their historical role, who acquire autonomy, authenticity, so that know how to solve problems, interact in their context, develop critical, self critical thinking and acquire authentic performances according to the demands of the curriculum. Based on a descriptive investigation with the use of theoretical and empirical methods, to a sample of 28 participants. The main result is achieved by providing didactic guides for the development of coastal folk dance; those that allowed increased the abilities, capacities and skills of the students.
Keywords: Folklore; Culture; cultural identity